1981
DOI: 10.1136/thx.36.6.424
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive response to pneumonectomy in puppies.

Abstract: When left pneumonectomy was performed on 9-week-old puppies, the right lung increased in weight, volume, surface area, and number of alveoli so that at age 20 weeks these variables were the same as those of both lungs of control animals and significantly larger than those of the right lung of control animals. The adaptive response of the right lung after pneumonectomy was greater in the lower lobe than in the middle or cardiac lobes. The number of alveoli per ml and the average interalveolar wall distance, hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…DLO2 was estimated by a modified version (13) of the previously established morphometric model (11,14). The model describes the gas diffusion path from alveolar air to the binding sites on hemoglobin as two serially linked conductance steps through the tissue and plasma barrier (Dbo2) and the erythrocyte (Deo2): DLoj ' = Dboj ' + Deoj' (1) where Dbo = Kbo0 (Sa + S.) (2) (21=hb) Sa and S, are the measured total alveolar and capillary surface area, and V. the measured total capillary blood volume. Thb is the harmonic mean thickness of the combined tissue and plasma barrier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DLO2 was estimated by a modified version (13) of the previously established morphometric model (11,14). The model describes the gas diffusion path from alveolar air to the binding sites on hemoglobin as two serially linked conductance steps through the tissue and plasma barrier (Dbo2) and the erythrocyte (Deo2): DLoj ' = Dboj ' + Deoj' (1) where Dbo = Kbo0 (Sa + S.) (2) (21=hb) Sa and S, are the measured total alveolar and capillary surface area, and V. the measured total capillary blood volume. Thb is the harmonic mean thickness of the combined tissue and plasma barrier.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally believed that postpneumonectomy compensatory lung growth occurs in immature dogs but not in fully mature dogs (1)(2)(3). In adult dogs, postpneumonectomy compensation is largely attributed to use of existing functional reserves in the remaining lung.…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the mean linear intercept (L M ) (representing the average distance between air space walls, or average airspace diameter), we used the formula LM = n -Lj'ei, where n is the number of lines counted, L is the length of the line, and ei is the sum of septal (walls of air spaces) intercepts. To calculate the ISA, we use the formul a ISA = 4· VL/LM , where VL is the postfixation lung volume by water displacement (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the cellular components which contribute to repair and remodelling of pulmonary tissue still await ultimate elucidation. Solutions to the problems concerning repair and regeneration of lung tissue for restoration of functional alveoli are at the cutting edge of identifying novel therapeutic options for lung diseases like chronic obstructive pulmonary disease (COPD) and fibrosis.It has been previously reported that partial resection of the lung results in a rapid compensatory growth process of the remaining lung tissue, restoring normal lung volume, cell mass and organ function, in a variety of mammalian species [2][3][4][5][6]. Compensatory lung growth following unilateral pneumonectomy (PNX) has been documented for dogs, rabbits, ferrets, rats and mice.…”
mentioning
confidence: 99%
“…It has been previously reported that partial resection of the lung results in a rapid compensatory growth process of the remaining lung tissue, restoring normal lung volume, cell mass and organ function, in a variety of mammalian species [2][3][4][5][6]. Compensatory lung growth following unilateral pneumonectomy (PNX) has been documented for dogs, rabbits, ferrets, rats and mice.…”
mentioning
confidence: 99%